1995
DOI: 10.1021/jm00018a020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and serotonergic activity of arylpiperazide derivatives of serotonin: potent agonists for 5-HT1D receptors

Abstract: A series of new arylpiperazide derivatives of serotonin has been prepared and evaluated as 5-HT1D receptor agonists. Binding experiments at cloned human 5-HT1D alpha, 5-HT1D beta, and 5-HT1A receptors show that all the compounds are very potent and selective ligands for 5-HT1D receptor subtypes. Functional activity studies (contraction of the New Zealand white rabbit saphenous vein) demonstrate that most of the derivatives behave as full agonists. Among them, the aryl sulfonamide derivative 5q (pD2 = 8.33 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…TLC was performed on 5 cmÂ10 cm aluminium plates coated with silice gel 60 F 254 (Merck) in an appropriate solvent. [14][15][16], 1 equiv of 8-9 and 1 equiv of TDAE in anhydrous DMF were stirred at À20 C for 1 h and then warmed up to 70 C for 2 h. b % All yields refer to the chromatographically isolated pure products and are relative to chloride 8-9. a Reaction conditions: 3 equiv of 23, 1 equiv of 8-9 and 1 equiv of TDAE in anhydrous DMF were stirred at À20 C for 1 h and then warmed up to rt for 3 h. b % All yields refer to the chromatographically isolated pure products and are relative to chloride 8-9.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…TLC was performed on 5 cmÂ10 cm aluminium plates coated with silice gel 60 F 254 (Merck) in an appropriate solvent. [14][15][16], 1 equiv of 8-9 and 1 equiv of TDAE in anhydrous DMF were stirred at À20 C for 1 h and then warmed up to 70 C for 2 h. b % All yields refer to the chromatographically isolated pure products and are relative to chloride 8-9. a Reaction conditions: 3 equiv of 23, 1 equiv of 8-9 and 1 equiv of TDAE in anhydrous DMF were stirred at À20 C for 1 h and then warmed up to rt for 3 h. b % All yields refer to the chromatographically isolated pure products and are relative to chloride 8-9.…”
Section: Generalmentioning
confidence: 99%
“…General procedure for the reaction of o-and p-nitrobenzyl derivatives 1, 4, 6-9 and a-halocarbonyl derivatives 2a-c 0 , [14][15][16]23 using TDAE. Into a two-necked flask equipped with a nitrogen inlet was added, under nitrogen at À20 C, 6 mL of anhydrous DMF solution of o-and p-nitrobenzyl derivative (2 mmol, 1 equiv) and corresponding a-halocarbonyl derivatives (2a: 2 equiv; 2b: 5 equiv; 2b 0 , 2c, 2c 0 , 14-16, 23: 3 equiv).…”
Section: Procedures For Tdae Reactionmentioning
confidence: 99%
“…This provided us with the rationale for our chemical approach. In taking advantage of the potency and efficacy characteristics of 5-HT compared with tryptamine at 5-HT 1B/1D receptors, F 11356 was synthesized as a novel arylpiperazide 5-HT derivative (22,24) (Fig. 1), which distinguishes F 11356 from the tryptamine derivatives from a chemical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…During our investigations toward the design and identification of selective 5-HT 1B/1D ligands, we have found that the 5- O -substitution of serotonin with arylpiperazide moieties through a carboxymethyl linker was a very efficient method to design potent, selective, and efficacious 5-HT 1B/1D agonists. This chemical modification of serotonin (which binds to at least 14 different receptor subtypes) into compounds of general formula 2 is a very efficient way to design selective 5-HT 1B/1D agonists. This observation suggests that 5-HT 1B/1D receptor subtypes possess a deep binding pocket in the binding domain recognizing the substituent attached in the 5- O -position of the serotonin residue.…”
Section: Introductionmentioning
confidence: 99%